Political trust in Europe: what it is and why it matters - Taylor, Isabel S.A. (2018)
Political trust is a vital resource in representative democracies. It helps citizens to forsake a degree of their personal autonomy to allow elected representatives to act on their behalf. Political trust therefore makes collective benefits possible and encourages citizens’ acceptance of policies, laws and regulations. But while the theoretical value of political trust has been widely set out, there is little empirical evidence to support the argument that political trust plays an important role in representative democracies. This is partly due to the difficulty in operationalizing and observing political trust accurately in survey research when survey respondents are unable to disentangle their political trust from their support for incumbent officeholders. The highly endogenous relationships between political attitudes further complicate attempts to identify causal relationships between related political attitudes. The papers in this thesis address these issues to demonstrate that political trust clearly has a significant and substantial impact on political life.